Pains Model in The Development Of Muslim Women-Friendly Tourist Destinations - Hakim, Lukmanul; Hafidzah, Ibna Azka; Susanto, Dedy; Savitri, Fania Mutiara (Lasigo Akademia Indonesia, 2025)
Muslim Women-Friendly Tourist Destinations are now a global trend in the tourism industry, driven by the need for inclusive travel and in accordance with Sharia values. Based on the Mastercard-CrescentRating Muslim Women in Travel (MWIT) 2019 report, more than 45% of Muslim travellers are. This figure shows that Muslim women have a huge influence on travel planning and decision-making. The Global Muslim Travel Index (GMTI) emphasizes the importance of developing tourist destinations that are friendly to Muslim women, aiming to create a safe, comfortable, and inclusive travel experience. This research uses the PAINS model, which considers privacy, facilities, identity, network, and security factors, to evaluate and determine tourist destinations that meet the needs of Muslim women. The research method used is qualitative, through interviews, observations, and literature review. Data sources include books, journal articles, news, the Global Muslim Travel Index (GMTI) reports from 2021 to 2024, and research reports related to the PAINS model. The results of this research indicate that safety and privacy are the main factors in the selection of tourist destinations for Muslim women, followed by the importance of the availability of places of worship and access to information about the local community. These findings emphasize the need for the integration of Muslim-friendly services in tourism policies to create inclusive and sustainable experiences. This research enriches the literature on Muslim-friendly tourism and provides practical recommendations for the development of the tourism sector in both OIC and non-OIC member countries to enhance the competitiveness and quality of tourist destinations globally.